Counting train-of-four twitch response: comparison of palpation to mechanomyography, acceleromyography, and electromyography. (June 2020) - Bowdle, Andrew; Bussey, Logan; Michaelsen, Kelly; Jelacic, Srdjan; Nair, Bala; Togashi, Kei; Hulvershorn, Justin
Abstract: Background: Train-of-four twitch monitoring can be performed using palpation of thumb movement, or by the use of a more objective quantitative monitor, such as mechanomyography, acceleromyography, or electromyography. The relative performance of palpation and quantitative monitoring for determination of the train-of-four ratio has been studied extensively, but the relative performance of palpation and quantitative monitors for counting train-of-four twitch responses has not been completely described. Methods: We compared train-of-four counts by palpation to mechanomyography, acceleromyography (Stimpod™), and electromyography (TwitchView Monitor™) in anaesthetised patients using 1691 pairs of measurements obtained from 46 subjects. Results: There was substantial agreement between palpation and electromyography (kappa = 0.80), mechanomyography (kappa = 0.67), or acceleromyography (kappa = 0.63). Electromyography with TwitchView and mechanomyography most closely resembled palpation, whereas acceleromyography with StimPod often underestimated train-of-four count. With palpation as the comparator, acceleromyography was more likely to measure a lower train-of-four count, with 36% of counts less than palpation, and 3% more than palpation. For mechanomyography, 31% of train-of-four counts were greater than palpation, and 9% were less. For electromyography, 15% of train-of-four counts were greater than palpation, and 12% were less. The agreement between acceleromyography and electromyography was fair (kappa = 0.38). For acceleromyography, 39% of train-of-four counts were less than electromyography, and 5% were more. Conclusions: Acceleromyography with the StimPod frequently underestimated train-of-four count in comparison with electromyography with TwitchView.